Los braquiópodos del tránsito Jurásico Inferior-Jurásico Medio de la Cuenca Lusitánica (Portugal) - Andrade, Benito (Coloquios de Paleontología, 2007)
Since the 18th century, the Lower Jurassic-Middle Jurassic transition Brachiopods from the Lusitanian Basin have been studied, there being a number of references dealing with partial aspects of Systematics, geographic distribution or chronological framework for this fauna. The present study includes a global approach to the brachiopods recorded in this basin within the stratigraphic interval ranging from the Upper Toarcian to the Lower Bajocian. For this purpose, an exhaustive sampling was carried out at different stratigraphic sections, representing the different environments developed during this time in the basin. As a result, a high number of specimens were collected, which were later prepared, studied and described, considering both external and internal morphology. During the Lower Jurassic-Middle Jurassic transition, the Lusitanian Basin developed an extensive, slightly sloping, open ramp. At the West of the basin, a submarine fan sequence is preserved related to the Berlengas Horst. In the ramp and the submarine fan, different sedimentary environments are recorded, representing different palaeoecological conditions and yielding different brachiopod fauna. The proximal, bioclastic sediments are observed in the Tomar area. The different parts of the carbonated ramp, where the lateral variation of facies indicate its orientation, opening towards the west, are represented by the sediments of Porto de Mós, Rabaçal, Coimbra and Cabo Mondego regions. The sediments of the submarine fan sequence can be observed in the Peniche region. A total of 24 brachiopod species belonging to 14 genera have been identified in the interval late Toarcian-early Bajocian of the Lusitanian Basin. As a result of the systematic study, twelve new species have been described as well as four new genera. The Order Rhynchonellida is represented in the Lower-Middle Jurassic transition of the Lusitanian Basin by 11 species. Three of these species belong to the genus Soaresirhynchia ALMÉRAS: the Toarcian species S. renzi (CHOFFAT in ALMÉRAS), and two new Aalenian species, S. minor sp. nov., characterised by its small size, and S. murtinheirensis sp. nov., which extends the distribution of the genus to the Bajocian. Another new species from the upper Toarcian, P.? jorali sp. nov., has been tentatively included in the genus Pamirorhynchia OVCHARENKO, which had a record up to now limited to the Pamir region. The genus Pseudogibbirhynchia AGER, was also recognised in the basin: P. bothenhamptonensis (WALKER) from the Upper Toarcian, and P. mutans (ROTHPLETZ) from the Aalenian. A new genus, Mondegia, is defined to include a new species: M. limica, a rhynchonellid from the lower Bajocian limestones of the Cape Mondego region. Another new species from the Toarcian, C. alcariensis sp. nov., is assigned to the genus Choffatirhynchia GARCÍA JORAL & GOY. Finally, the Superfamily Norelloidea is represented in the basin by two Toarcian genera; Praemonticlarella GARCÍA JORAL, with a new species, P. conimbrigensis sp. nov., and Nannirhynchia BUCKMAN, with two local species, N. cotteri (CHOFFAT in ALMÉRAS et al.) and N. delgadoi (CHOFFAT in ALMÉRAS et al.). Regarding the Order Terebratulida, 13 different species are represented in the basin within the referred chronological interval. Two species belong to the genus Stroudithyris BUCKMAN: S. stephanoides ALMÉRAS & MOULAN, common in the Upper Toarcian and lower Aalenian in the Mediterranean area, and S. choffati sp. nov., recorded in the lower Bajocian of the Cape Mondego region. A peculiar group of terebratulids recorded in the lower Bajocian of the Cape Mondego region has been described as a new species and a new genus: Lusothyris atlantica gen. nov., sp. nov. Two frequent taxa in nearby basins, Lophrothyris withingtonensis (BUCKMAN) from the middle-upper Aalenian, and Loboidothyris perovalis (SOWERBY) from the lower Bajocian, were also recognised in the Lusitanian Basin. Another widely distributed genus, Sphaeroidothyris BUCKMAN, is represented in the basin by three species; S. vari (ROLLIER), common in the middle-upper Toarcian of the “Spanish Bioprovince of Brachiopods”; S. uretae GARCÍA JORAL, a species known from the Aalenian of the Iberian basin, and a new species present only in the Aalenian- Lower Bajocian of the basin: S. henriquesae sp. nov. As for the Zeilleroidea, four species were included into the genus Neozeilleria gen. nov., described to group the small-sized zeillerids which appear after the mass extinction that takes place in the lower Toarcian. Two of these species were previously included in the genus Zeilleria BAYLE: N. anglica (OPPEL), a well-known species from the European Aalenian, and N. sharpei (CHOFFAT), only known from the Lusitanian and Iberian basins. The other two species, N. duartei sp. nov. and N. nuskae sp. nov., are typical from the upper Toarcian of the Lusitanian Basin. Finally, a new Laqueoidea from the lower Bajocian was described; Lusitanina bituminis gen. nov., sp. nov., a small brachiopod recorded at rich in organic matter marls from the Cape Mondego region. The stratigraphic distribution of the different taxa of brachiopods from the Lusitanian Basin is established for the niddle Toarcian – lower Bajocian interval. A biozonation based on these distributions is proposed, and compared with those established for the neighbouring basins. The paleobiogeographic relationships of the brachiopod fauna of the Lusitanian Basin and those of other basins, from the Protoatlantic to the Pamir, are analysed and discussed, leading to a proposal of a dispersion model for the brachiopod groups along the North Tethyan coast. The relevant differences observed in the brachiopod assemblages, related to the various sedimentary and palaeoecological environments, have been used to reconstruct a pattern relating the distribution of these assemblages with distinct areas of the carbonate ramp and the submarine fan sequence of Peniche in the Lusitanian Basin. The evolution of brachiopod assemblages along the upper Toarcian-lower Bajocian interval shows three distinct episodes: starting from the lower Toarcian typical fauna of the “Spanish Bioprovince of Brachiopods”, a decline both in diversity and abundance is observed at the end of the Toarcian, with relatively poor and endemic assemblages. After a faunistic turnover in the Opalinum Zone, new assemblages appear, including new species that frequently belong to the same genera present in the assemblages previous to the turnover.